The relationship between coping strategies and quality of life in breast cancer patients undergoing chemotherapy - Yuanita, Irma Linda; Sumarni; Dasuki, Djaswadi (BKM Public Health and Community Medicine, 2021)
Purpose: The purpose of this study is to determine the relationship between coping strategies and the quality of life of breast cancer patients undergoing chemotherapy at RSUD Prof. Dr. W.Z. Johannes Kupang, East Nusa Tenggara. Methods: This study used a cross-sectional design involving 59 breast cancer patients undergoing chemotherapy as respondents. The chi-square test was used for bivariate analysis, and logistic regression was used for multivariate analysis. Results: There is a relationship between emotion-focused coping strategies (p=0.000; PR=4.7; 95% CI: 1.87-11.9) and problem-focused coping strategies (p=0.000; PR=5.0; 95% CI: 2.0-12.7) with the quality of life of breast cancer patients undergoing chemotherapy at RSUD Prof. Dr. W.Z. Johannes Kupang, East Nusa Tenggara. After considering the variables of education, occupation, family income, and cancer stage, there is a relationship with quality of life, whereas age and marital status do not have a relationship with the quality of life of breast cancer patients undergoing chemotherapy. Conclusion: The quality of life of breast cancer patients undergoing chemotherapy at RSUD Prof. Dr. W.Z. Johannes Kupang, East Nusa Tenggara can be improved by maximizing coping strategies.